Synagogue paintings as indicating a!developing conception of national redemption - Orgad, Zvi (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Abstract. Orgad Zvi, Synagogue paintings as indicating a developing conception of national redemption. “Images” vol. XXV, no. 34. Poznań 2019. Adam Mickiewicz University Press. Pp. 15–27. ISSN 1731-450X. DOI 10.14746/i.2019.34.01. This article compares the interior paintings in the ‘Ades and Ohel Moshe synagogues, both of which are non-Ashkenazi, in the Naḥlaot neighborhood in Jerusalem. Although the synagogues were decorated 50 years apart, there are similarities in the painted motifs and drawing schemes, but also some differences. I suggest that these differences reflect the development of a Jewish concept of national redemption during the 50 years that elapsed between the adornment of the two synagogues.